Changes in treatment outcomes in patients undergoing an integrated psychosomatic inpatient treatment: Results from a cohort study - Sadlonova, Monika; Löser, Julia Katharina; Celano, Christopher M.; Kleiber, Christina; Broschmann, Daniel; Herrmann-Lingen, Christoph (Frontiers in Psychiatry, 2022)
Objective. In Germany, multimodal psychosomatic inpatient treatment can be initiated for patients with substantial mental disorders (e.g., depression, anxiety, somatoform disorders) and comorbid physical disease. However, studies investigating changes in psychological and functional treatment outcomes, and predictors of long-term treatment effects in patients undergoing psychosomatic inpatient treatment are needed. Methods. This cohort study analyzed 160 patients aged ≥ 18 who were treated on an integrated psychosomatic inpatient unit at the University of Göttingen Medical Center. Its aim was to analyze changes in psychological and functional outcomes, and to identify predictors of long-term improvements in health-related quality of life (HRQoL) in patients with comorbid mental and physical illness who were undergoing integrated inpatient psychosomatic treatment. Assessments were completed at admission, discharge, and 12- or 24-month follow-up. Outcomes included physical complaints (Giessen Subjective Complaints List [GBB-24]), psychological symptoms (Brief Symptom Inventory [BSI]), and HRQoL (European Quality of Life Questionnaire [EQ-5D]). Results. One-hundred sixty inpatients were included (mean age = 53.1 ± 12.6; 53.8% female). There were significant, medium- to large-sized improvements in psychological symptoms (BSI-Global Severity Index; d=-0.83, p<0.001), physical symptom burden (d=-0.94, p<0.001), and HRQoL (d=0.65, p<0.001) from admission to discharge, and significant, small- to medium-sized greater improvements in all psychological outcomes from admission to follow-up (BSI-GSI: d=-0.54, p<0.001; GBB-24 total symptom burden: d=-0.39, p<0.001; EQ-5D: d=0.52, p<0.001). Furthermore, better improvement in HRQoL during hospitalization (partial η2=0.386; p < 0.001) was associated with higher HRQoL at follow-up. Finally, intake of antidepressant at discharge was associated with impaired HRQoL at follow-up (η2=0.053; p=0.03). Conclusions. There were significant short- and long-term improvements in psychological symptoms, physical complaints, and HRQoL after treatment on an integrated psychosomatic inpatient unit in patients with mental disorders and a comorbid physical disease.